Perbedaan Pola Konsumsi Fast Food Dan Soft Drink PadaRemaja Putri Overweight Dan Non OverweightDi SMA Assalam Surakarta - Rahmi, Nada (2016)
Introduction: Arecently, overweight become a health problem world wide, affecting not only developed countries but also developing countries such as Indonesia . Increased prevalence of overweight due to changes in diet. Pattern The increasing of fast food in the food industry in Indonesia could affect eating patterns of adolescents . Fast food generally contains high energy , fat , sugar , and sodium (Na) , but low in fiber and micronutrients . Another factor that can increase the risk of overweight is the consumption of soft drinks containing high sugar . Purpose:The purpose of this study was to determine the differences between fast food and soft drink consumption pattern on overweight and non overweight adolescents at Assalam High School Surakarta. Method:This was an observational study with cross sectional approach . The population was high school students at Assalam, Surakarta grade X and XI (189 students). The sample in this study were 66 students ( 33 overweight and 33 non overweight) obtained by random sampling . Data analysis using Mann Whitney test and Kolmogorov Smirnov Results:Research shows that overweight adolescents (57.6%) had a rare frequency of fast food consumption and non- overweight adolescents (72.7%) had a very rare frequency of fast food consumption. Overweight adolescents (51.5%) had a lot of total energy of fast food comsumption and non- overweight adolescents (81.8%) had a little total energy of fast food comsumption. Overweight adolescents (69.7%) had a rare frequency of soft drink consumption and non- overweight adolescents (75.8%) had a very rare frequency of soft drink consumption. Overweight adolescents (66.7%) had a lot of total energy of soft drink comsumption and non overweight adolescents (87.9 %) had a little total energy of fast food comsumption . Conclusion:There are differences in the frequency of fast food consumption, total energy consumption of fast food , the frequency of soft drink consumption, and the total energy consumption of soft drinks in overweight and non overweight adolescents ( p = 0.001 , p = 0.001 , p = 0.001 and p = 0.002 ). Key Word:Fast Food Consumption Patterns , Soft Drink Consumption Patterns , adolescents , Overweight and Non Overweight References: 57, 1997 - 2014